Brief Report: Causes of Stillbirths in Women With Systemic Lupus Erythematosus. Issue 10 (28th September 2016) - Vinet, Évelyne; Genest, Geneviève; Scott, Susan; Pineau, Christian A.; Clarke, Ann E.; Platt, Robert W.; Bernatsky, Sasha
Abstract : Objective: There are few precise or recent estimates of the risk or causes of stillbirths in women with systemic lupus erythematosus (SLE). Thus, we undertook the present study to examine causes of stillbirths in mothers with SLE versus those without SLE. Methods: The Offspring of SLE Mothers Registry (OSLER) is a large population‐based cohort, identified through Quebec's health care databases (1989–2009), including all women who had ≥1 hospitalization for delivery after SLE diagnosis, and a randomly selected control group of women matched for age and year of delivery. We identified stillbirths and ascertained the cause of death as indicated on death certificates. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated, and multivariate logistic regression analysis was performed to estimate the risk of stillbirth in women with SLE versus controls. Results: In our cohort, 509 women with SLE had 729 births, including 9 stillbirths, while 5, 829 matched controls had 8, 541 births, including 47 stillbirths. We observed more stillbirths in mothers with SLE than in controls (1.24% versus 0.55%, difference 0.69% [95% CI 0.03, 1.88]). Women with SLE had an increased risk of stillbirth compared to controls (adjusted OR 2.13 [95% CI 1.02, 4.45]). We also observed a trend toward more stillbirths due to placenta‐mediated pregnancy complications in mothers with SLE than in controls (44% [95% CI 14, 79] versus 15% [95% CI 6, 28]). Conclusion: Compared to women from the general population, women with SLE have an increased risk of stillbirth. Stillbirths in women with SLE might be more often caused by placenta‐mediated pregnancy complications compared to stillbirths in mothers without SLE.